1995
DOI: 10.1128/mcb.15.9.4702
|View full text |Cite
|
Sign up to set email alerts
|

Four Subunits That Are Shared by the Three Classes of RNA Polymerase Are Functionally Interchangeable between Homo sapiens and Saccharomyces cerevisiae

Abstract: Four cDNAs encoding human polypeptides hRPB7.0, hRPB7.6, hRPB17, and hRPB14.4 (referred to as Hs10␣, Hs10␤, Hs8, and Hs6, respectively), homologous to the ABC10␣, ABC10␤, ABC14.5, and ABC23 RNA polymerase subunits (referred to as Sc10␣, Sc10␤, Sc8, and Sc6, respectively) of Saccharomyces cerevisiae, were cloned and characterized for their ability to complement defective yeast mutants. Eukaryotic mRNAs are synthesized by large transcription complexes formed by RNA polymerase II and a number of protein cofactors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
112
0
6

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 55 publications
(72 reference statements)
1
112
0
6
Order By: Relevance
“…Plasmids are listed in Table I. pGEN-13MYC was constructed by directional cloning of the 552 nt BamHI-EcoRI fragment from pFA6 -13MYC (25) in the yeast expression vector pGEN (30). pVV101 is a pGEN-13MYC derivative obtained by PCR cloning of the TFA1 coding sequence at the BamHI site upstream of the 13MYC epitope.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids are listed in Table I. pGEN-13MYC was constructed by directional cloning of the 552 nt BamHI-EcoRI fragment from pFA6 -13MYC (25) in the yeast expression vector pGEN (30). pVV101 is a pGEN-13MYC derivative obtained by PCR cloning of the TFA1 coding sequence at the BamHI site upstream of the 13MYC epitope.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, purified RNA polymerase II from S. pombe contains 10 polypeptides (Sakurai et al 1996) and up to the present time, we have cloned and sequenced the genes encoding three large core subunits, Rpb1, Rpb2 and Rpb3 (Azuma et al 1991;Kawagishi et al 1993;Azuma et al 1993) and five small subunits, Rpb5, Rpb7, Rpb8, Rpb10, and Rpb11 (this paper, H. Sakurai & A. Ishihama, in preparation). Shpakovski (1994) and Shpakovski et al (1995) isolated the genes encoding Rpb6 and Rpb12.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these differences, some mechanistic similarities are apparent. The three RNA polymerases share five common subunits and other subunits that are highly related (Woychik et al 1990;McKune et al 1995;Shpakovski et al 1995), whereas the TATA-binding protein (TBP) is shared by three RNA polymerase type-specific accessory factors (Struhl 1994). Studies with isolated components have shown ordered pathways for the assembly of RNA polymerases and cognate initiation factors into active preinitiation complexes (for review, see Zawel and Reinberg 1995;Roeder 1996a).…”
mentioning
confidence: 99%